Prevention of Exercise-induced Asthma by a Fixed Combination of Disodium Cromoglycate plus Reproterol Compared with Montelukast in Young Patients - Lecheler, Josef; Pfannebecker, Bernhard; Nguyen, Duc Tung; Petzold, Ursula; Munzel, Ullrich; Kremer, Hans-Joachim; Maus, Joachim (Arzneimittelforschung, 2008)
The leukotriene inhibitor montelukast has been recommended against exercise-induced asthma (EIA), however, single-dose agents might be favourable in several aspects.To compare the protective effects against EIA of a single inhalation of the combination disodium cromoglycate (DSCG, CAS 16110-51-3) and reproterol (REP, CAS 54063-54-6) with 3 days oral treatment of montelukast (MON, CAS 158966-92-8).Open-label, cross-over, single-centre trial. Twenty-four 6 to 18-year-old children and adolescents, with reversible and stable airway obstruction, baseline FEV1, > 70 %, predicted and proven EIA (i.e. a maximum decrease of FEV1 by ≥ 20% compared with baseline) were treated with MON, orally for 3 days in the evening, or one single inhalation of DSCG/REP 20 min before the exercise challenge. The treatment sequence was randomised. The exercise test on a treadmill was performed under standardised conditions.24 patients completed both periods. Both treatments clearly provided protection against EIA; however, protection of DSCG/REP was more pronounced than that of MON. This difference was statistically significant even if the data were adjusted for the increase in FEV1 between inhalation of DSCG/REP and challenge (DSCG/REPadjusted). The nadir FEV1, level after exercise following prophylaxis with DSCG/REP was even higher than the pre-inhalation FEV1, value. From these data, protection indices of 66 %, 81 %, and 113% for MON, DSCG/REPadjusted, and DSCG/REPunadjusted, respectively, were estimated.Inhalation of DSCG/REP before exercise provides significantly better protection against EIA than three days treatment with MON.
Keywords: Antiasthmatic drugs; CAS 16110-51-3; CAS 54063-54-6; CAS 158966-92-8; Disodium cromoglycate; Exercise-induced asthma, children; Montelukast; Reproterol